To Feel That Thirty Years Is Nothing: The Role of Volver Channel in The Management and Dissemination of Audiovisual Television Archives - Adduci Spina, Elina (Millcayac - Revista Digital de Ciencias Sociales, 2025)
Thirty years after the creation of Volver, this article reflects on the channel’s role in the preservation of Argentine television audiovisual memory. The institutions linked to Canal 13 are studied with the purpose of unraveling the political-institutional plot that outlined its production and its archive. Subsequently, the management model of Volver is examined to analyze the mechanisms of a memory policy based on the nostalgic recovery of a cultural identity shaped by a hegemonic environment. Likewise, the uses of archives are investigated with the mission of evaluating the hybridization processes that place them between tradition and current culture.